2020
DOI: 10.3389/fmicb.2020.00526
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized Membrane Domains: An Ancestral Feature of Archaea?

Abstract: Bacteria and Eukarya organize their plasma membrane spatially into domains of distinct functions. Due to the uniqueness of their lipids, membrane functionalization in Archaea remains a debated area. A novel membrane ultrastructure predicts that monolayer and bilayer domains would be laterally segregated in the hyperthermophilic archaeon Thermococcus barophilus. With very different physico-chemical parameters of the mono-and bilayer, each domain type would thus allow the docking of different membrane proteins a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 79 publications
(106 reference statements)
1
41
0
Order By: Relevance
“…This IPL composition contrasts with those previously reported for this species, although PI-DGD II was systematically the most abundant IPL detected [ 21 , 22 ]. GMGT-based CL [ 4 , 25 , 26 ] and IPL [ 33 ] have been identified in numerous archaea, including some Thermococcales but, to the best of our knowledge, our study constitutes the first identification of GMGT-based lipids in P. furiosus and the first report of PI-GMGT0-PI XXIV and PI-GTGT0-PI XX as archaeal IPL. By contrast, Sprott et al [ 21 ] tentatively identified PG-based IPL, such as PG-DGD VIII and dihexose(2Hex)-GDGT0-PG XII ( Figure 1 ), in addition to PI-DGD II and PHexNAc-DGD III.…”
Section: Discussionmentioning
confidence: 85%
See 4 more Smart Citations
“…This IPL composition contrasts with those previously reported for this species, although PI-DGD II was systematically the most abundant IPL detected [ 21 , 22 ]. GMGT-based CL [ 4 , 25 , 26 ] and IPL [ 33 ] have been identified in numerous archaea, including some Thermococcales but, to the best of our knowledge, our study constitutes the first identification of GMGT-based lipids in P. furiosus and the first report of PI-GMGT0-PI XXIV and PI-GTGT0-PI XX as archaeal IPL. By contrast, Sprott et al [ 21 ] tentatively identified PG-based IPL, such as PG-DGD VIII and dihexose(2Hex)-GDGT0-PG XII ( Figure 1 ), in addition to PI-DGD II and PHexNAc-DGD III.…”
Section: Discussionmentioning
confidence: 85%
“…However, a variety of cyclopentane ring-containing tetraethers, including GTGT with 1 and 2 rings (GTGT1 and 2, XXI and XXII, respectively), GDGT with 1 to 4 rings (GDGT1 to 4, XIII, XV, XVII and XVIII, respectively) and GMGT with 1 to 4 rings (GMGT1 to 4, XXV to XXIIIV, respectively), was obtained upon acidic methanolysis of P. furiosus lipid extract, pre-extracted cells and biomass ( Figure 3 A–C). Correcting for the response factor for diethers relative to tetraethers [ 26 ], we determined that the most abundant CL in the three different methanolysates of P. furiosus were DGD I (ca. 44%, 45% and 36%, respectively) and GMGT0 XXIII (ca.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations